2016
DOI: 10.1099/jgv.0.000415
|View full text |Cite
|
Sign up to set email alerts
|

Morbillivirus and henipavirus attachment protein cytoplasmic domains differently affect protein expression, fusion support and particle assembly

Abstract: The amino-terminal cytoplasmic domains of paramyxovirus attachment glycoproteins include trafficking signals that influence protein processing and cell surface expression. To characterize the role of the cytoplasmic domain in protein expression, fusion support and particle assembly in more detail, we constructed chimeric Nipah virus (NiV) glycoprotein (G) and canine distemper virus (CDV) haemagglutinin (H) proteins carrying the respective heterologous cytoplasmic domain, as well as a series of mutants with pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 63 publications
2
14
0
Order By: Relevance
“… 41 To evaluate the applicability of the VLP-based immunization approach for the production of high-titer antisera against other emerging viruses, NiV VLPs were generated by co-transfecting HEK-293T cells with plasmids encoding the NiV matrix protein (M) in combination with either the F or G protein of the NiV Malaysia strain. 42 After 48 h, supernatant was harvested, purified and concentrated via ultracentrifugation. The resulting NiV-M/G and NiV-M/F VLP preparations showed no distinct bands migrating in Coomassie-stained sodium dodecyl sulfate-polyacrylamide gel electrophoresis (SDS-PAGE) gels (Fig.…”
Section: Resultsmentioning
confidence: 99%
“… 41 To evaluate the applicability of the VLP-based immunization approach for the production of high-titer antisera against other emerging viruses, NiV VLPs were generated by co-transfecting HEK-293T cells with plasmids encoding the NiV matrix protein (M) in combination with either the F or G protein of the NiV Malaysia strain. 42 After 48 h, supernatant was harvested, purified and concentrated via ultracentrifugation. The resulting NiV-M/G and NiV-M/F VLP preparations showed no distinct bands migrating in Coomassie-stained sodium dodecyl sulfate-polyacrylamide gel electrophoresis (SDS-PAGE) gels (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…One of our studies showed that chimeras containing the NiV-G head domain and the NDV HN stalk domain could bind ephrinB2 and trigger fusion mediated by NDV F (28). In the present study, to elucidate the protein elements responsible for the fusion phenotypes observed, we created G chimeras in which we exchanged the CT/TM/stalk (residues 1 to 167) or head (residues 168 to 604) domain between HeV and NiV G. Functional properties of the cytoplasmic, stalk, and head domains of G have been described somewhat (54)(55)(56)(57). Our G chimeras revealed that the CT/TM/stalk domain of HeV G is a main determinant of the hypofusogenic NF/HG phenotype and that this may in part be attributed to a stronger binding avidity of the HG CT/TM/stalk domain to NF.…”
Section: Discussionmentioning
confidence: 96%
“…The low abundance of M protein arrays in the tomograms was hypothesized to represent disassembly of the arrays after budding is complete to facilitate subsequent membrane fusion and particle uncoating [6], but could alternatively also originate from specimen preparation, storage, and/or cryo-preservation. While the presence of functional M protein and intact glycoprotein cytoplasmic tails can down-modulate cell-to-cell fusion activity of some paramyxoviruses [65,66,67], it is unclear whether F refolding is indeed suppressed through F tail contact with intact M protein arrays as was speculated [6]. However, it is difficult to envision the subsequent introduction of extreme negative membrane curvature required for lipid merger and opening of a fusion pore [68] in the presence of an intact M protein lattice, necessitating the partial or complete breakdown of the arrays at some point prior to infection.…”
Section: Interaction Of the M Protein With The Rnp Complexmentioning
confidence: 99%